Magnesium fluoride nanofiber film as well as preparation method and application thereof

By uniformly coating magnesium fluoride nanoparticles on nanocellulose, magnesium fluoride nanofiber film is prepared, which solves the problems of dendrites growth and electrolyte reactivity during the cycle of lithium metal batteries, and achieves the stability and energy density of lithium metal batteries.

CN119875170AActive Publication Date: 2025-04-25HUNAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510087616.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

During the circulation process, existing lithium metal batteries have problems with battery life and safety due to the high reactivity of organic electrolytes and the growth of lithium dendrites. In addition, traditional magnesium fluoride particle coating methods have problems with weakening of activity and uneven distribution.

Method used

By uniformly coating magnesium fluoride nanoparticles on nanocellulose, a flexible self-supported magnesium fluoride nanofiber film is prepared. Using the three-dimensional network structure and film-forming characteristics of the nanocellulose, a uniform magnesium fluoride coating layer is formed to protect the lithium metal negative electrode.

Benefits of technology

The magnesium fluoride nanofiber film can promote uniform deposition of lithium metal, inhibit the growth of lithium dendrites, improve the cycle stability and energy density of lithium metal batteries, and has good flexibility and self-supporting capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875170A_ABST
    Figure CN119875170A_ABST
Patent Text Reader

Abstract

The invention provides a magnesium fluoride nanofiber film as well as a preparation method and application thereof. The film-forming characteristic and the nanofiber mesoporous network of the nanocellulose material are utilized in a high-valued manner, and the characteristic that the magnesium fluoride material and the lithium metal spontaneously form lithium-loving sites and lithium fluoride is combined, so that the material can be used as a functional interlayer of the lithium metal battery to protect a lithium metal negative electrode. When used as a lithium metal light and thin protective layer, a uniform ion transmission path and a lithium fluoride interface protective layer are formed on the surface of lithium metal to promote uniform deposition of the lithium metal and inhibit growth of lithium dendrites, so that the cycling stability of a lithium metal negative electrode is greatly improved, and the lithium metal negative electrode material is expected to be used for constructing a long-service-life and high-energy-density lithium metal battery. According to the invention, the nano cellulose, magnesium fluoride and the lithium metal battery are organically connected together, and the unique effect of the magnesium fluoride nano fiber in a lithium metal protection interface is explored, so that the cycle performance of the lithium metal battery is greatly improved, and the rate capability of the battery is improved; and the preparation process is simple and low in energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a magnesium fluoride nanofiber film and a preparation method and application thereof. Background Art

[0002] Rechargeable lithium metal batteries have the advantages of high theoretical energy density, low electrochemical potential, light weight and good electrochemical cycle stability, and are widely used in the field of energy storage. However, in the secondary metal battery cycle, such as lithium metal batteries, the high reactivity of organic electrolytes and the uncontrolled dendrite growth of lithium metal anodes lead to the problem of dendrites penetrating the diaphragm, which seriously affects the life and safety of lithium metal batteries.

[0003] In order to reduce the continuous side reactions between lithium metal anodes and organic electrolytes and the growth of lithium dendrites, the design of a strong and chemically stable solid electrolyte interface (SEI) on the surface of lithium metal anodes has attracted extensive attention and research from researchers. Among them, inorganic solid electrolyte interfaces rich in lithium fluoride are considered to be the key passivation films for stabilizing lithium metal systems. Since the fluorine-containing functional groups have strong electron absorption, the lowest unoccupied molecular orbital energy of fluorine-containing substances is lower than that of organic solvents. They can decompose preferentially before other solvents and form lithium fluoride with lithium on the surface of the anode, which can hinder the contact and reaction between the lithium metal surface and the organic electrolyte. In addition, studies have shown that the presence of metal alloy phases at the interface of lithium metal anodes can promote uniform lithium metal deposition and increase the diffusion coefficient of lithium ions. Among them, magnesium metal particles have infinite solubility with lithium metal, can achieve ultra-low or zero nucleation overpotential, and are conducive to uniform lithium deposition / stripping, thereby inhibiting the growth of lithium dendrites.

[0004] Based on the gain effect of fluorine-containing functional groups and metal fluorides in lithium metal batteries, many researchers combine the two substances in the hope of achieving the effect of 1+1>2. Magnesium fluoride can react with lithium metal in situ electrochemically to form lithium-philic lithium-magnesium alloy and lithium fluoride, a component of the stable SEI layer, thereby inducing uniform deposition of lithium metal and inhibiting the growth of lithium dendrites. To achieve this effect, many researchers have recently used magnesium fluoride nanoparticles coated on polypropylene diaphragms for diaphragm modification or directly coated on the surface of lithium metal negative electrodes to construct LiF-rich SEI. However, due to the powder characteristics of magnesium fluoride particles, they often rely on binders to be coated on the surface of diaphragms or lithium metal, resulting in the activity of magnesium fluoride particles being weakened by the coverage of the binder. At the same time, the particles are unevenly distributed and have gaps, resulting in uneven distribution of reaction sites and ions, affecting the generation of a highly uniform SEI layer. Therefore, the method of directly using magnesium fluoride particles to improve the stability of lithium metal negative electrodes has limitations.

[0005] The inventor's previous work shows that cellulose materials are derived from forest grasses, and hydroxyl groups are evenly distributed on their surfaces. They have a three-dimensional network structure with uniform pore size distribution, papermaking film-forming properties, and degradability, which provides the possibility for designing a flexible self-supporting interface protective layer with uniform void characteristics. For example, patent authorization number CN115149209B discloses that cellulose extracted from common plants in nature is combined with zirconium ions to make modified nanocellulose membranes, which significantly improve the rate performance of aqueous zinc ion batteries or lithium ion batteries. However, the above patent only utilizes the ionic crosslinking effect between the zirconium ions of soluble zirconium salts and the hydroxyl groups on the surface of nanocellulose. In essence, it is still a nanocellulose material, which uses a porous three-dimensional network to improve ion transmission, does not react with the lithium metal negative electrode, and is difficult to regulate the physical and chemical properties of the lithium metal interface electrolyte interface membrane, and cannot effectively protect lithium metal, so its application in high energy density lithium metal batteries is limited.

[0006] To this end, we hope to develop a self-supporting magnesium fluoride nanofiber film with uniform pore size, anti-lithium dendrite, and lithium metal electrolyte interface film to protect lithium metal. Summary of the invention

[0007] The present invention provides a magnesium fluoride nanofiber film and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.

[0008] In order to achieve the above-mentioned purpose, the embodiment of the present invention provides a magnesium fluoride nanofiber film and its preparation method and application. The present invention uses nanocellulose as a template for the first time, uniformly coats magnesium fluoride nanoparticles on nanocellulose, and prepares a flexible self-supporting magnesium fluoride nanofiber film, making full use of the intrinsic nanofiber mesoporous network and film-forming properties of nanocellulose to obtain a magnesium fluoride nanofiber film. It is used for a lightweight self-supporting protective film for lithium metal, which can induce uniform lithium metal deposition and generate a LiF-rich SEI, significantly improving the cycle stability of lithium metal batteries. The present invention uses biomass cellulose to prepare magnesium fluoride nanofiber films in a high-value manner. The uniformly distributed hydroxyl functional groups on the cellulose ensure the uniform coating of magnesium fluoride nanoparticles, and the prepared nanocellulose film uniformly coated with magnesium fluoride nanoparticles is flexible, self-supporting, lightweight, and has uniform void characteristics. The magnesium fluoride nanofiber film can homogenize lithium ions and induce the formation of uniform lithium metal deposition. At the same time, it reacts with lithium metal in situ to form a lithium-philic lithium-magnesium alloy with a high lithium ion diffusion coefficient and a uniform LiF-rich solid electrolyte interface film (SEI), thereby inhibiting the growth of lithium dendrites and improving the cycle stability of lithium metal batteries.

[0009] An object of the present invention is to provide a method for preparing a magnesium fluoride nanofiber film, comprising the following steps:

[0010] S1: adding nanocellulose powder and soluble magnesium salt into deionized water, and obtaining a nanocellulose suspension containing magnesium ions after ultrasonic dispersion;

[0011] S2: adding soluble fluoride to the nanocellulose suspension containing magnesium ions, stirring and reacting, and obtaining a magnesium fluoride nanofiber film through suction filtration, washing and drying;

[0012] The nanocellulose surface of the magnesium fluoride nanofiber film has a uniform and dense magnesium fluoride coating layer.

[0013] Preferably, the soluble magnesium salt is any one of magnesium acetate, magnesium chloride, magnesium nitrate or magnesium sulfate, and the concentration is 1 to 60 mmol / L.

[0014] Preferably, the soluble fluoride is any one of potassium fluoride, ammonium fluoride and sodium fluoride, and the concentration is 1 to 60 mmol / L.

[0015] Preferably, the stirring reaction time is 1 to 24 hours.

[0016] Preferably, the drying temperature is 40-120° C., and the drying time is 6-48 hours.

[0017] Based on a general concept of the invention, an embodiment of the present invention provides a magnesium fluoride nanofiber film obtained by the above-mentioned preparation method. The magnesium fluoride nanofiber film is intended to form a uniform and dense magnesium fluoride coating layer on the surface of nanocellulose, which can react with lithium metal in situ electrochemically to form a lithium-philic lithium-magnesium alloy to promote the uniform nucleation and growth of lithium metal, and generate a solid electrolyte interface film SEI rich in LiF, inhibit the growth of lithium dendrites, effectively regulate the lithium metal deposition regulation behavior, and further improve the rate cycling characteristics of lithium metal batteries.

[0018] Preferably, the porosity of the magnesium fluoride nanofiber film is 30% to 60%.

[0019] Preferably, the magnesium fluoride nanofiber film has a thickness of 1 to 60 μm.

[0020] Preferably, the diameter of the nanofibers in the magnesium fluoride nanofiber film is between 30 and 80 nm.

[0021] An embodiment of the present invention further provides a magnesium fluoride nanofiber film obtained by the above-mentioned preparation method or the use of the above-mentioned magnesium fluoride nanofiber film in a lithium metal battery.

[0022] Reaction mechanism

[0023] The invention adopts nanocellulose as a template and prepares a magnesium fluoride nanofiber film through magnesium fluoride modification. The film has the characteristics of high mechanical strength, good flexibility, high thermal stability, controllable porosity, uniform and flat surface, light weight and good lyophilic ability, etc., and can be used as a battery separator interlayer to form a dense and uniform deposition layer on the surface of the lithium negative electrode, forming a lithium-magnesium alloy with a high lithium ion diffusion coefficient and a solid electrolyte interface film SEI rich in lithium fluoride with a certain mechanical strength, which can hinder the direct contact reaction between lithium metal and organic electrolyte and inhibit the generation of lithium dendrites in the cycle process, thereby extending the cycle stability of the lithium metal battery; the magnesium fluoride nanofiber film of the invention directly forms a dense magnesium fluoride nanoparticle coating layer on the surface of the nanocellulose on the basis of inheriting the platform advantages of the processability and papermaking film-forming property of the nanocellulose solution. When the magnesium fluoride nanofiber film contacts lithium metal, it can react in situ at the lithium metal negative electrode to generate a lithium-magnesium alloy with a high lithium ion diffusion coefficient and a lithium fluoride-rich solid electrolyte interface film with good mechanical strength, inducing uniform deposition of lithium metal and inhibiting the growth of lithium dendrites. It has been verified that the magnesium fluoride nanofiber film can inhibit side reactions on the electrode surface, reduce lithium sheet corrosion, and inhibit lithium dendrite growth.

[0024] The above scheme of the present invention has the following beneficial effects:

[0025] (1) Compared with the original nanocellulose film, the magnesium fluoride nanofiber film of the present invention has a unique uniform network of magnesium fluoride that can react with lithium metal in situ to form a lithium-philic lithium-magnesium alloy to promote the uniform nucleation and growth of lithium metal, and generate a LiF-rich solid electrolyte interface film SEI, inhibiting the growth of lithium dendrites, effectively regulating the lithium metal deposition behavior, and further improving the rate cycling characteristics of lithium metal batteries.

[0026] (2) Compared with the traditional lithium metal interface protection method based on magnesium fluoride particles, the magnesium fluoride nanofiber film of the present invention is flexible and self-supporting, has a three-dimensional nanofiber network structure and uniform mesopore distribution, is light and thin, and conforms to the current development trend of thin and light functional lithium metal protection films. The thickness and porosity of the magnesium fluoride nanofiber film of the present invention can be adjusted to 1 μm, which is significantly lower than conventional particle-based functional coatings, and is conducive to improving the overall energy density of lithium metal batteries.

[0027] (3) The preparation process of the magnesium fluoride nanofiber film of the present invention is simple, and it fully inherits the intrinsic platform advantages of nanocellulose materials. The above scheme of the present invention reveals that inorganic non-metallic magnesium fluoride nanofibers can be prepared using nanocellulose as a one-dimensional template. The intrinsic hydroxyl functional groups on the nanocellulose are conducive to the uniform coating of magnesium fluoride nanoparticles. The prepared magnesium fluoride nanofiber film has uniform pore characteristics, which can promote electrolyte infiltration, homogenize lithium ion distribution and accelerate lithium ion transmission, induce uniform deposition of lithium metal, and is conducive to improving the cycle performance of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 is a scanning electron microscope image of the magnesium fluoride nanofiber film provided by an embodiment of the present invention;

[0030] Figure 2 is a scanning electron microscope image of nanocellulose provided in a comparative example of the present invention;

[0031] Figure 3 XRD patterns of magnesium fluoride nanofiber film provided by the embodiment of the present invention compared with the original nanocellulose film;

[0032] Figure 4 Schematic diagram of the contact angle of the magnesium fluoride nanofiber film provided in an embodiment of the present invention compared with the original nanocellulose film; (a) is a schematic diagram of the contact angle of the magnesium fluoride nanofiber film, and (b) is a schematic diagram of the contact angle of the original nanocellulose film;

[0033] Figure 5 The magnesium fluoride nanofiber film provided in the embodiment of the present invention is used as an interlayer to compare the original nanocellulose film for lithium metal symmetric battery at 1 mA cm -2 The current density is 1 mAh cm -2 Cycling performance diagram under area capacity. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0035] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0037] Herein, “CNF” refers to pristine nanocellulose, and “CNF@MgF2” refers to magnesium fluoride nanofiber film.

[0038] In view of the existing problems, the present invention provides a magnesium fluoride nanofiber film and a preparation method and application thereof.

[0039] Example 1

[0040] This embodiment provides a method for preparing a magnesium fluoride nanofiber film.

[0041] The method of this embodiment specifically includes the following steps:

[0042] (1) Weighing 50 mg of nanocellulose powder and 200 mg of magnesium chloride powder, mixing, adding a certain amount of water and performing ultrasonic dispersion to obtain a nanocellulose suspension containing magnesium ions;

[0043] (2) adding excess ammonium fluoride to the nanocellulose suspension containing magnesium ions, stirring for 6 hours, setting up a suction filtration device, directly filtering to form a film, and heating and drying in an oven, and peeling off to obtain a magnesium fluoride nanofiber film, the SEM image of which is shown in FIG. Figure 1 As shown, the thickness is basically the same at all locations, which is 27 μm, and the porosity is ∼60%.

[0044] Comparative Example 1

[0045] In the absence of nanocellulose in the synthesis, 200 mg of magnesium chloride powder was weighed, mixed and dissolved with a certain amount of water, and then an excess of ammonium fluoride was added. After stirring for 6 hours, a filtration device was built and the mixture was directly filtered and dried. Only powdered magnesium fluoride was obtained, and the particles were of different sizes. In the absence of a binder, a smoothly laid magnesium fluoride interface protective layer could not be obtained, and it could only exist in powder form.

[0046] Comparative Example 2

[0047] The difference from Example 1 is that 50 mg of nanocellulose powder is weighed and added with a certain amount of water for ultrasonic dispersion, a suction filtration device is built, and the nanocellulose film is directly filtered and heated and dried in an oven to obtain a nanocellulose film, the SEM image of which is shown in FIG. Figure 2 shown.

[0048] Comparative Example 3

[0049] The difference from Example 1 is that 50 mg of nanocellulose powder and 200 mg of magnesium fluoride powder are weighed, a certain amount of deionized water is added, ultrasonic dispersion is performed, stirring is performed for 6 hours, a filtration device is built, and a film is directly filtered and formed, and the film is heated and dried in an oven, and peeled off to obtain a composite film of magnesium fluoride and nanocellulose, the thickness of which is uneven, about 36 to 45 μm.

[0050] Comparative Example 4

[0051] The difference from Example 1 is that magnesium chloride powder is replaced with zinc chloride powder, and other steps and parameters are the same as those in Example 1. Ultimately, zinc fluoride nanoparticles cannot be coated on the surface of nanocellulose, and zinc fluoride particles are not obtained. Since the intrinsic hydroxyl functional groups on the surface of nanocellulose interact differently with different metal ions, the hydroxyl functional groups on nanocellulose are conducive to the uniform coating of magnesium fluoride nanoparticles, while zinc fluoride is not.

[0052] Comparative Example 5

[0053] The difference from Example 1 is that the magnesium chloride powder is replaced with aluminum chloride powder, and the other steps and parameters are the same as those in Example 1. In the end, aluminum fluoride nanoparticles cannot be coated on the surface of nanocellulose, and zinc fluoride particles are not obtained. The intrinsic hydroxyl functional groups on the surface of nanocellulose interact differently with different metal ions. The hydroxyl functional groups on cellulose are conducive to the uniform coating of magnesium fluoride nanoparticles, while aluminum fluoride is not.

[0054] like Figures 1 to 2 As shown, Figure 2 It is a nanocellulose film, whose fibers are interwoven to form a three-dimensional cross-linked network with uniform pores, and the fiber diameter is 10 to 30 nm; Figure 1 It is a magnesium fluoride nanofiber film. The fibers are significantly thicker, with a diameter of 30 to 80 nm. A uniformly distributed nanoparticle coating layer appears on the surface of the nanocellulose, retaining the three-dimensional pore structure of the original nanocellulose.

[0055] from Figure 3 It can be seen from the XRD spectrum that the characteristic peak of cellulose in the magnesium fluoride nanofiber film of the present invention is reduced compared with the original nanocellulose. This is because the magnesium fluoride particles are coated on the fiber surface, which shields part of the signal of the characteristic peak of cellulose. According to the characteristic peak of the magnesium fluoride XRD standard card PDF#41-1443, it can be shown that magnesium fluoride is successfully coated on the surface of nanocellulose.

[0056] like Figure 4 As shown in the contact angle diagram, the contact angle of the magnesium fluoride nanofiber film of the present invention is 19°, while the contact angle of the original cellulose film is 37°, indicating that the magnesium fluoride nanofiber film has better electrolyte wettability.

[0057] The magnesium fluoride nanofiber film obtained in the example and the original nanocellulose film were used as interlayers in a lithium metal symmetric battery. The lithium metal symmetric battery was -2 The current density is 1 mAh cm -2 The area capacity is cycled, such as Figure 5As shown, the lithium metal battery with magnesium fluoride nanofiber film as interlayer has a smaller polarization voltage and a longer cycle life, indicating that the magnesium fluoride nanofiber film can promote the uniform deposition of lithium metal and inhibit the growth of dendrites.

[0058] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a magnesium fluoride nanofiber film, characterized in that: The steps include: S1: adding nanocellulose powder and soluble magnesium salt into deionized water, and obtaining a nanocellulose suspension containing magnesium ions after ultrasonic dispersion; S2: adding soluble fluoride to the nanocellulose suspension containing magnesium ions, stirring and reacting, and obtaining a magnesium fluoride nanofiber film through suction filtration, washing and drying; The nanocellulose surface of the magnesium fluoride nanofiber film has a uniform and dense magnesium fluoride coating layer.

2. The method for preparing a magnesium fluoride nanofiber film according to claim 1, characterized in that: The soluble magnesium salt is any one of magnesium acetate, magnesium chloride, magnesium nitrate or magnesium sulfate, and the concentration is 1-60 mmol / L.

3. The method for preparing a magnesium fluoride nanofiber film according to claim 1, characterized in that: The soluble fluoride is any one of potassium fluoride, ammonium fluoride and sodium fluoride, and the concentration is 1-60 mmol / L.

4. The method for preparing a magnesium fluoride nanofiber film according to claim 1, characterized in that: The stirring reaction time is 1 to 24 hours.

5. The method for preparing a magnesium fluoride nanofiber film according to claim 1, characterized in that: The drying temperature is 40-120° C., and the drying time is 6-48 hours.

6. A magnesium fluoride nanofiber film obtained by the preparation method according to any one of claims 1 to 5.

7. The magnesium fluoride nanofiber film according to claim 6, characterized in that: The porosity of the magnesium fluoride nanofiber film is 30% to 60%.

8. The magnesium fluoride nanofiber film according to claim 6, characterized in that: The thickness of the magnesium fluoride nanofiber film is 1-60 μm.

9. The magnesium fluoride nanofiber film according to claim 6, characterized in that: The diameter of the nanofibers in the magnesium fluoride nanofiber film is between 30 and 80 nm.

10. Use of a magnesium fluoride nanofiber film obtained by the preparation method according to any one of claims 1 to 5 or a magnesium fluoride nanofiber film according to any one of claims 6 to 9 in a lithium metal battery.

Citation Information

Patent Citations

  • A method for preparing and applying a zirconium ion-modified nanocellulose paper-based battery separator

    CN115149209B

  • Lithium metal negative electrode carbon-based main body material and preparation method thereof

    CN116314737A

  • Isolating membrane, preparation method thereof, and related secondary battery and electric device

    CN117015901A

  • Hoe holder for convenience of laser marking work

    KR1020250107023A

  • Polyolefin base film and preparation method therefor, separator, secondary battery and electric device

    WO2024087132A1